KEWAJIPAN PENCARUM TAKAFUL MEMBAYAR ZAKAT: SATU PENILAIAN SEMULA : The Obligation of Takaful Contributors to Pay Zakat: A Reassessment - Amat Zainordin, Nurul Syahirah; Buang, Ahmad Hidayat; Daud, Mohd Zaidi; Jamaludin, Mohd Hafiz; Purkon, Arip (Jurnal Syariah, 2024)
Nowadays, various Islamic financial products, including takaful, are subject to zakat obligations. Takaful products, particularly Family Takaful, are among the Islamic financial offerings in Malaysia that contain elements of wealth liable for zakat based on their savings and investment components. This study aims to analyze the zakat rulings on family takaful contributions by considering the views of Islamic scholars, current practices, and contemporary fatwas. The study employs a qualitative approach using library-based data to obtain accurate information on the research questions. The methodology of content analysis is a qualitative approach employed in this study, involving the examination of texts, documents, and descriptive data. This methodology is applied to assess the necessity of zakat obligations for takaful contributors. The analysis adopts a systematic process to comprehend the concepts, principles, and implementation of zakat for takaful contributors. The findings indicate that takaful funds, whether in the form of investments, savings, or compensation, are categorized as either savings or income. When the pillars and conditions of zakat, particularly nisab and haul, are fulfilled, zakat becomes obligatory on the participants or their beneficiaries. Considering that the purpose of takaful is protection and risk management, this article seeks to re-evaluate the obligation of zakat on takaful based on the eligibility criteria, particularly conditions such as exceeding basic needs, being free from debt, and full ownership.